Ketidakadilan Budaya Patriarkhi terhadap Perempuan di Nias - Yurulina Gulo (Universitas Negeri Medan, 2019)
The writing of this journal aims to give a new view of how a woman who in Ono Niha mythology has very high respect, but in reality the woman in Nias is the object of injustice in the culture of Patriarchy that has been formed for a long time in Nias. In this journal, using a descriptive-analytical approach with a qualitative approach. The qualitative approach emphasizes the accuracy of data, it will use an inductive approach, which means that data will be collected, approached, and abstracted through interviews, literature and field observations. Thus the authors obtain data that in Nias, women experienced oppression in a real patriarchal culture because of the social construction that made it number two and regarded as weak and low based on the nature of the natural label. The oppression experienced by women in society socially, politically and religiously. The basis of the injustice in society in various fields is rooted in the culture of patriarchy where men assume that women belong to their property, servants and complementaries.